2008
DOI: 10.1093/chemse/bjn014
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Processing of Odors: Evidence for a Nonlinear Relation between Pleasantness and Familiarity Evaluations

Abstract: Pleasantness, familiarity, and intensity are 3 interdependent dimensions commonly used to describe the perceived qualities of an odor. In particular, many empirical studies have demonstrated a positive correlation between familiarity and pleasantness. However, on the basis of both theoretical and methodological perspectives, we questioned the validity of such a relation for malodors. We report 2 studies based on subjective judgments of a large sample of odorants (Experiment 1) associated with autonomic recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 48 publications
7
84
1
4
Order By: Relevance
“…One way to tackle this issue would be to present another odor that would be neutral enough not to constitute a primary reward but would be similarly rich to the chocolate in term perceptual characteristic. However, given the vast interindividual variability in hedonic odor perception (e.g., Delplanque et al, 2008;Distel et al, 1999;Ferdenzi et al, 2013), it appears very difficult to find a consensual neutral odor. Moreover, the learning process to associate two neutral stimuli is different from the one to associate an emotional stimulus with a neutral one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to tackle this issue would be to present another odor that would be neutral enough not to constitute a primary reward but would be similarly rich to the chocolate in term perceptual characteristic. However, given the vast interindividual variability in hedonic odor perception (e.g., Delplanque et al, 2008;Distel et al, 1999;Ferdenzi et al, 2013), it appears very difficult to find a consensual neutral odor. Moreover, the learning process to associate two neutral stimuli is different from the one to associate an emotional stimulus with a neutral one.…”
Section: Discussionmentioning
confidence: 99%
“…Participants evaluated, on a visual analogue scale presented on the screen, the pleasantness (from ''extremely unpleasant'' to ''extremely pleasant''), familiarity (from ''not familiar at all'' to ''extremely familiar''), edibility (from ''not edible'' to ''extremely edible''), and intensity (from ''not perceived'' to ''extremely strong'') of the chocolate odor and of the odorless air (e.g., Delplanque et al, 2008;Khan et al, 2007). Subsequently, they answered questions about chocolate (back translated to French from Rolls & McCabe, 2007) that allowed investigation of whether participants associated chocolate with the two components of reward (Berridge & Robinson, 2003): motivation (i.e., ''On a scale from 1 to 10, how much would you say that you sometimes crave chocolate?'')…”
Section: Manipulation Checkmentioning
confidence: 99%
“…This was performed to keep the odor set at an overall satisfactory level of familiarity in these cultures, not to miss any important but culture-dependent odor-elicited responses, and thus to favor the elicitation of affective feelings as they occur in everyday contexts. The odorous substances, provided by Firmenich SA, Geneva, were diluted in odorless dipropylene glycol to obtain similar subjective intensities (see Delplanque et al 2008;Chrea et al 2009). Pen-like devices (Sniffin' Sticks, Burghart Gmbh, Germany) were filled with 7 ml of each diluted solution and coded with a 3-digit number.…”
Section: Scale Constructionmentioning
confidence: 99%
“…It has been demonstrated that there is a positive correlation between perceived odorant intensity, familiarity and pleasantness [10], although familiarity and pleasantness are associated in a complex way [11]. Recently, a gustatory semantic link has been shown in a brain fMRI study that the subject gustatory cortices are activated by only reading the semantic of the word 'salt', whose meaning is related to a particular taste [12].…”
Section: Introductionmentioning
confidence: 99%